2020
DOI: 10.1002/ejic.201901179
|View full text |Cite
|
Sign up to set email alerts
|

Homopolyatomic Chalcogen Radical Cations of Selenium and Tellurium

Abstract: The stability of selenium and tellurium homopolyatomic radical cations in the gas phase and liquid sulfur dioxide solution was estimated using density functional theory (DFT). First of all, the structures of the neutral, cationic, and dicationic homopolyatomic chalcogen clusters [Ch x ] y+ (Ch = Se, Te; x = 3-10, y = 0-2) were optimized in the gas phase. The stability of the currently unknown radical cations [Ch x ] + against various decomposition reactions (e.g. disproportionation, dimerization) was predicted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 78 publications
0
1
0
Order By: Relevance
“…Consequently, the experimentally and theoretically unknown corresponding radical cations of the chalcogen elements sulfur, selenium, and tellurium [Ch x ] + (Ch = S, Se, Te, x = 2-10) became of interest. In a very recent theoretical account, we have shown that some radical cations of the heavier chalcogens selenium and tellurium should also be experimentally accessible in condensed phases (Jenne & Nierstenhö fer, 2020). Modern weakly coordinating anions such as perhalogenated closo-dodecaborates (Knapp, 2013) are expected to be suitable counter-anions for homopolyatomic chalcogen radical cations in solution and the solid state.…”
Section: Chemical Contextmentioning
confidence: 99%
“…Consequently, the experimentally and theoretically unknown corresponding radical cations of the chalcogen elements sulfur, selenium, and tellurium [Ch x ] + (Ch = S, Se, Te, x = 2-10) became of interest. In a very recent theoretical account, we have shown that some radical cations of the heavier chalcogens selenium and tellurium should also be experimentally accessible in condensed phases (Jenne & Nierstenhö fer, 2020). Modern weakly coordinating anions such as perhalogenated closo-dodecaborates (Knapp, 2013) are expected to be suitable counter-anions for homopolyatomic chalcogen radical cations in solution and the solid state.…”
Section: Chemical Contextmentioning
confidence: 99%